Aspek Ideational, Interpersonal, Social, dan Textual dalam Pembelajaran Pendidikan Agama Islam - Ismail (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
The teacher is the key to the success of an educational institution. The good or bad behavior or teaching methods of teachers will greatly affect the image of educational institutions. the focus of this study rests on the ideational, interpersonal, social, and textual aspects of Islamic Education Learning. This research uses